Oral cavity principal founlain of dispertion of Helicobacter pylori - Moromi Nakala, Hilda (2005)
This Micro-Revision includes the presentation and interpretation of the advances in the knowledge related to the Helicobacter pylori in the oral cavity, as a reservoir and source of the recurrence of the bacterial oction. It IS been planned that the necessity of conceiving control and eradication strategies in the buccal cavity, in order to improve the success of the eradication treatment of the gastroduodenal bacteria.